Effects of Smoking Ban Regulations on Individual Smoking Rates - Wilkins, R; Buddelmeyer, H (My University, 2005)
This paper describes the dynamics of smoking behaviour in Australia and investigates what impact smoking ban regulations have, if any, on individual smoking patterns. Such legislation receives a lot of press attention when announced and introduced, but its effect on individuals’ smoking behaviour has received little research attention. The main argument used to motivate the introduction of tougher smoking bans is reducing exposure of non-smokers to second hand smoke. From a public policy perspective it is important to know if these policies also affect whether people smoke, or if they only influence when and where people smoke. The Household, Income and Labour Dynamics in Australia (HILDA) survey data allow us to track individuals’ smoking behaviour over the period 2001 to 2003, during which time smoking ban initiatives in Queensland, Victoria and the Northern Territory came into effect. We exploit this variation over time and across states to assess the impact of tougher smoking regulations. Our findings indicate that smoking is strongly correlated with education, gender, early life experiences, alcohol consumption, income, and other characteristics. Conditional on being a smoker in the previous period, we find that the single biggest predictor of quitting is pregnancy. Few other characteristics are able to explain who quits. Conditional on not smoking in the previous period, people who drink daily or weekly and couples who separated or divorced between the previous and current periods are most likely to take up smoking. The effect of the introduction of smoking ban regulations on individuals’ smoking behaviour is generally in the expected direction, albeit not statistically significant for most types of individual. However, we find a significant ‘rebellion’ effect among 18 to 24 year old smokers, with the introduction of smoking bans found to increase the likelihood that they continue to smoke.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Melbourne Institute Working Papers
Keywords: Health; Policy; Health -- Addictive behaviours; Health and wellbeing; Health